Labor informality in Norte de Santander, Nariño, La Guajira and Cesar - Colombia (2016)
The article aims to analyze labor informality from a regional context including the states of border areas, through two kinds of methodology: non-parametric and parametric. Within the non-parametric methodology it is used the arc elasticity and in the parametric it is used panel data method. The results show a positive relationship between the participation of industrial GDP, the Gini coefficient, the monetary poverty and informal work for the states under review.